Complying with Regulations to Sell Farm Fresh Eggs - Brad Burbaugh; Elena Toro; Linda Landrum; George L. Harrison; John Fruin; Allen Wysocki (EDIS, 2010)
FE828, a 4-page illustrated fact sheet by Brad Burbaugh, Elena Toro, Linda Landrum, George Harrison, John Fruin, and Allen Wysocki, provides an overview of the steps necessary to comply with Florida’s existing regulations for selling eggs which are overseen by FDACS. Published by the UF Department of Food and Resource Economics, February 2010.